The Economics of Fertility: A New Era - Matthias Doepke; Anne Hannusch; Fabian Kindermann; Michèle Tertilt (Institute of Labor Economics (IZA), 2022)
In this survey, we argue that the economic analysis of fertility has entered a new era. First-generation models of fertility choice were designed to account for two empirical regularities that, in the past, held both across countries and across families in a given country: a negative relationship between income and fertility, and another negative relationship between women's labor force participation and fertility. The economics of fertility has entered a new era because these stylized facts no longer universally hold. In high-income countries, the income-fertility relationship has flattened and in some cases reversed, and the cross-country relationship between women's labor force participation and fertility is now positive. We summarize these new facts and describe new models that are designed to address them. The common theme of these new theories is that they view factors that determine the compatibility of women's career and family goals as key drivers of fertility. We highlight four factors that facilitate combining a career with a family: family policy, cooperative fathers, favorable social norms, and flexible labor markets. We also review other recent developments in the literature, and we point out promising new directions for future research on the economics of fertility.
Keywords: D13; J13; J16; 330; fertility; family economics; marital bargaining